A new insular species of Cyrtodactylus (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia - Grismer, L. Lee; Ahmad, Norhayati (Zootaxa, 2008)
A new species of the gekkonid lizard, Cytrodactylus macrotuberculatus sp. nov., is described from Pulau Langkawi of the Langkawi Archipelago located off the northwest coast of Peninsular Malaysia in the state of Kedah. This species had been previously recognized as C. pulchellus but is differentiated here from that species and all other Sunda Shelf Cyrtodactylus on the basis of its strong tuberculation and other scale and color pattern characteristics. This represents the second endemic species known from the Langkawi Archipelago.